South Africa - The Roundabout Outdoor Playpump - Field, Trever (World Bank, Washington, DC, 2012)
Hand pumps are physically grueling for women and wasteful of a strained resource. Now a patented South African invention the Roundabout Playpump simplifies the whole exercise by providing a maintenance-free pump that is easy to use and provides many other social and environmental benefits.